Managing Cultural And Language Differences: Ethnographic Study Of NTT Congregation Within HKBP Suprapto Church - Yolanda Natasia Letare; Tiara Annisa Zephania; Nasya Putri Amaranggana; Amanda Ibel Anzela; Almira Adani Rusman (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
In the midst of the dominance of Batak culture, the HKBP Suprapto Church functions as a multicultural space that unites various backgrounds, including congregations from NTT. Using an ethnographic approach and Communication Accommodation Theory (CAT) theory by Howard Giles, this study explores communication strategies such as convergence, divergence, and maintenance of cultural identity carried out by these minority congregations. Data were collected through participatory observation and in-depth interviews of worship activities and social interactions in the church. The results of the study show that the NTT congregation performs various forms of communication adaptation to build social relations without losing their cultural identity. The role of the church as a social space is able to facilitate cultural diversity and encourage harmony between congregations. This research also fills the gap in the previous study by examining the dynamics of identity negotiation in cross-cultural religious communities.